Religiosity, interpersonal attachment, and forgiveness among the Javanese population in Yogyakarta, Indonesia - Nashori, Fuad (Mental health, religion & culture, 2020)
This study aimed to examine forgiveness among the Javanese population in Yogyakarta, Indonesia. The proposed hypothesis was that a model of religiosity and interpersonal attachment would affect forgiveness, and agreeableness, and neuroticism would function as mediating variables. Three hundred and thirty-five individuals participated in the study. Data were collecting with a questionnaire on forgiveness, neuroticism, agreeableness, religiosity, and interpersonal attachment. The results showed that the model fit the data reasonably well. Thus, demonstrating that religiosity and interpersonal attachment affect forgiveness through agreeableness and neuroticism in the Javanese population in Yogyakarta. Furthermore, it was found that to improve forgiveness among this population, agreeableness should be maximised and neuroticism should be minimised.